A Real-Time Robust Fuzzy-based Level Control Using Programmable Logic Controller - Aydogmus, Zafer (Kaunas Univ Technology, 2015)
Industrial software are specially designed to meet specific process. And sometimes this software can be very expensive. One way to reduce this cost is to develop own algorithm. This paper presents a real-time liquid level control implementation for an industrial process. The implementation of the level control is achieved using a fuzzy-based control algorithm. A Programmable Logic Controller (PLC) was used in which the fuzzy control algorithm has been embedded and can withstand against abrupt changes in the outlet flow. In addition, the fuzzy control algorithm is introduced to the system without a fuzzy module or software package. As a consequence, a robust and low cost liquid level control system has been realized. A Mamdani Fuzzy Inference System (MFIS) has been proposed. Membership functions of the input and output variables of the system were obtained and verified using Matlab/Simulink environment. The obtained functions have been used for the construction of fuzzy control algorithm in PLC. A robust fuzzy-based level controller has been achieved and quite satisfactory results were obtained in real-time implementation for different outlet flow rates.
Keywords: Fuzzy control; level control; process control; robust control; real time systems